AB0083 Arthritis Induces Early Bone Structural Degradation and Mechanical Weakness. (15th July 2016) - Vidal, B.; Cascão, R.; Lopes, I.; Finnila, M.; Saarakkala, S.; Canhão, H.; Fonseca, J.E.
Abstract : Background: We have previously found in the chronic SKG mouse model of arthritis that long standing (5 and 8 months) inflammation directly leads to high collagen bone turnover, disorganization of the collagen network, disturbed bone microstructure and ultimately declining of bone biomechanical properties [1]. Objectives: Our main goal was to study the effects of the inflammatory process on the microarchitecture and mechanical properties of bone in the early stages of arthritis development. Methods: Fifty Wistar adjuvant-induced arthritis (AIA) rats were monitored throughout arthritis development and sacrificed after 4, 11 and 22 days of disease induction. Thirty healthy non-arthritic rats, age and sex-matched, were sacrificed at the end of the experiment and used as controls for comparison. The inflammatory score, ankle perimeter and body weight were measured over the experimental period. At the time of sacrifice, bone and serum samples were collected for micro-CT and 3-point bending analysis as well as bone turnover markers (CTX-I and P1NP), respectively. All experiments were approved by the Animal User and Ethical Committees at the Instituto de Medicina Molecular (Lisbon University), according to the Portuguese law and the European recommendations. Results: We have observed that bone turnover markers, CTX-I and P1NP, increased soon after arthritis onset (p<0.0001 and p=0.0034, respectively, when compared to healthy controls). Moreover, micro-CT analyses showed both in trabecular and cortical parameters, that the effects of inflammation on bone microstructure were evident since the 4th day of arthritis development. Of particular interest, trabecular bone volume fraction decreased and cortical porosity increased at day 22 post disease induction when comparing to healthy controls (p=0.0001 and p<0.0001, respectively). Biomechanical tests revealed that arthritic bone have altered biomechanical properties, such as maximal bending force (arthritic group lower than healthy control, p<0.0001). Conclusions: The inflammatory process induced bone loss, and reduces bone strength since the very early phase of arthritis. References: Caetano-Lopes J, Nery AM, Canhao H, Duarte J, Cascao R, et al. (2010) Chronic arthritis leads to disturbances in the bone collagen network. Arthritis Res Ther 12: R9. Disclosure of Interest: None declared